Penerapan Fatwa DSN-MUI Nomor 77/DSN-MUI/V/2010 pada Akad Murabahah pada Produk Cicil Emas di Bank Syariah Indonesia Panyabungan - Jureid (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2023)
The purpose of this study was to determine the application of the DSN-MUI Fatwa Number 77/DSN-MUI/V/2010 on the Murabahah Contract of Gold Installment Products at the Indonesian Sharia Bank Panyabung. The research method used is a descriptive method with a qualitative nature that aims to explain and describe how the research is. The implementation of the murabahah contract at Bank Syariah Indonesia Panyabungan is in accordance with the procedure. The customer will receive a copy of the SBKE, the original is stored at SDB BSI, until the customer pays off the gold purchased with the murabahah contract which has been determined according to the contract that has been signed according to the contract used. This process is in line with DSN MUI Fatwa No. 77/DSN-MUI/V/2010 concerning buying and selling gold in cash, and making gold as collateral with a rahn contract and stored in the hasanah safe of Bank Syariah Indonesia Panyabungan. The selling price that has been set at the beginning of the contract will not increase or decrease during the installment period even if the maturity occurs because the price of gold is set on the day when the contract takes place. The gold is used as rahn during the installment period. This means that the gold is kept in the bank until the installment period has ended, so the customer can own the gold. Gold that has been pledged may not be pledged again in a new contract